Model Penguatan E-dakwah Di Era Disruptif Melalui Standar Literasi Media Islam Online - Rila Setyaningsih (Universitas Darussalam Gontor, 2019)
Abstract The emergence of the disruptive era brings many changes in various aspects of life, including da’wah activities. Innovation methods and media of da’wah are important to do as an effort to strengthen the existence of da'wah in the development of the 4.0 industrial revolution era, basically an industrial revolution of 4.0 characterized by a cyber physic system and the Internet of Things. The existence and development of online media is a challenge as well as an opportunity for da'wah activities in the disruptive era. Strengthening e-da'wah or da'wah with the help of information and communication technology is important to adjust to the demands and needs of the times. The purpose of this study is to offer a model of strengthening e-da'wah in the disruptive era. This study uses descriptive qualitative methods. Data collection is done through documentation and literature studies. The results of the study were in the form of a model of strengthening e-da'wah in the disruptive era through the implementation of seven online Islamic media literacy standards. The seven standards were composed of the principles of online news production, the ethics of news distribution, the guarantee of accuracy and anti-hoax commitment, the spirit of amar ma'ruf nahi munkar, the principles of wisdom in da'wah, principles in digital interaction, and the principle of press freedom. The contribution of this research is a model of strengthening e-da'wah in the disruptive era through the implementation of seven online Islamic media literacy standards. Keywords: E-dakwah, Disruptive era, Online Islamic Media Literacy Standards. Abstrak Munculnya era disruptif membawa banyak perubahan dalam berbagai aspek kehidupan, tidak terkecuali dalam kegiatan dakwah. Inovasi metode dan media dakwah penting dilakukan sebagai upaya untuk memperkuat eksistensi dakwah di tengah perkembangan era revolusi industri 4.0, pada dasarnya revolusi industri ditandai dengan cyber physic system dan Internet of Things. Keberadaan dan perkembangan media online menjadi tantangan sekaligus peluang kegiatan dakwah di era disruptif. Penguatan e-dakwah atau dakwah dengan bantuan teknologi informasi dan komunikasi internet penting dilakukan untuk menyesuaikan diri terhadap tuntutan dan kebutuhan zaman. Tujuan penelitian ini untuk menawarkan sebuah model penguatan e-dakwah di era disruptif. Penelitian ini menggunakan metode kualitatif deskriptif. Pengumpulan data dilakukan melalui dokumentasi dan studi literatur. Hasil penelitian berupa model penguatan e-dakwah di era disruptif melalui implementasi tujuh standar literasi media Islam online. Tujuh standar tersebut meliputi prinsip produksi berita online, etika distribusi berita, jaminan akurasi dan komitmen anti hoax, spirit amar ma’ruf nahi munkar, asas hikmah dalam dakwah, prinsip dalam interaksi digital, dan prinsip kemerdekaan pers. Kontribusi penelitian ini adalah model penguatan e-dakwah di era disruptif melalui implementasi tujuh standar literasi media Islam online.Kata Kunci: E-dakwah, , Era Disruptif, Standar Literasi Media Islam Online.